Photothermal Actuators: Photothermal Bimorph Actuators with In‐Built Cooler for Light Mills, Frequency Switches, and Soft Robots (Adv. Funct. Mater. 27/2019). (2nd July 2019) - Li, Jingjing; Zhang, Rui; Mou, Linlin; Jung de Andrade, Monica; Hu, Xiaoyu; Yu, Kaiqing; Sun, Jinkun; Jia, Tianjiao; Dou, Yuanyuan; Chen, Hong; Fang, Shaoli; Qian, Dong; et al.
Abstract : In article number1808995, Zunfeng Liu and co‐workers develop a tri‐layered bimorph actuator that shows a fast response, large bending amplitude, and small temperature change. Building on these advancements, a light‐mill based on the wing‐flapping mechanism upon light irradiation is designed.